2004
DOI: 10.1002/cncr.20646
|View full text |Cite
|
Sign up to set email alerts
|

Anagrelide for thrombocytosis in myeloproliferative disorders

Abstract: The ectodermal dysplasias (ED) are a large and complex group of diseases characterized by anomalies of the ectoderm and its derivates, often associated with malformations in other organs. We report a patient with an ectodermal dysplasia affecting hair, teeth, and nails and malformations of all four extremities including absence of several rays in the hands and feet. This patient shares many similarities with odontotrichomelic syndrome, a rare ectodermal dysplasia syndrome that has so far only been described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…It reduces platelet production by inhibiting megakaryocyte colony development, thus reducing megakaryocyte size, ploidy and maturation [63]. Several studies have shown that it effectively lowers platelet counts (overall response rate of 76-94%) and reduces ET-associated complications and symptoms [63][64][65][66][67][68][69][70][71][72]. Anagrelide has been shown in trials to be as effective as hydroxycarbamide, interferon-α and alkylating agents in reducing platelet counts, without the added complication of alkylating or cytotoxic properties [73], and can be used in patients who are intolerant or resistant to these cytoreductive agents [64].…”
Section: Anagrelidementioning
confidence: 99%
See 3 more Smart Citations
“…It reduces platelet production by inhibiting megakaryocyte colony development, thus reducing megakaryocyte size, ploidy and maturation [63]. Several studies have shown that it effectively lowers platelet counts (overall response rate of 76-94%) and reduces ET-associated complications and symptoms [63][64][65][66][67][68][69][70][71][72]. Anagrelide has been shown in trials to be as effective as hydroxycarbamide, interferon-α and alkylating agents in reducing platelet counts, without the added complication of alkylating or cytotoxic properties [73], and can be used in patients who are intolerant or resistant to these cytoreductive agents [64].…”
Section: Anagrelidementioning
confidence: 99%
“…The ANAHYDRET study demonstrated non-inferiority of anagrelide (for efficacy and ET-related complications) compared with hydroxycarbamide for the treatment of ET patients at 12 months follow-up (p<0.025) [34]. Furthermore, in a study of 79 patients with ET, anagrelide significantly reduced the rate of major thromboembolic complications compared with the pre-treatment period (p=0.0455) [65]. However, a clear clinical benefit in terms of haemorrhagic events has not yet been convincingly demonstrated.…”
Section: Anagrelidementioning
confidence: 99%
See 2 more Smart Citations
“…Both drugs are potentially leukaemogenic -at least when being used sequentially in this patient group [69][70][71]. In younger patients alpha-interferon, PEG-Intron or anagrelide may be useful alternatives [72][73][74][75][76][77]. Since all these agents have side effects -and some even potentially leukaemogenic -several clinical trials have recently been conducted to find alternative and better drug formulations [78][79][80][81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 99%